2013
DOI: 10.4028/www.scientific.net/kem.569-570.88
|View full text |Cite
|
Sign up to set email alerts
|

Consumed Fatigue Life Assessment of Composite Material Structures by Optical Surface Roughness Inspection

Abstract: A strong knowledge of the fatigue state of highly advanced carbon fiber reinforced polymer composite (CFRP) structures is essential to predict the residual life and optimize intervals of structural inspection, repairs, and/or replacements. Current techniques are based mostly in measurement of structural loads throughout the service life by electric strain gauge sensors. These sensors are affected by extreme environmental conditions and by fatigue loads in such a way that the sensors and their systems require e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous studies [17,18] have shown that the magnitude of the surface roughness increases due to changes in the topography that have been induced by the damage. The changes of the surface start at the beginning of the life of the structure with matrix micro-cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [17,18] have shown that the magnitude of the surface roughness increases due to changes in the topography that have been induced by the damage. The changes of the surface start at the beginning of the life of the structure with matrix micro-cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Panels of 2 mm thickness in a quasi-isotropic stacking sequence of ((45,90,−45,0) s ) 2 , have been autoclave cured at 6 bars and 130 °C for 2.5 h. The ultimate tensile strength ( S ut ) of the material is 938 MPa and was determined statistically in a previous study [14]. Coupons with “dog bone” design, shown in Figure 2, were cut from the panels in order to guarantee the highest level of stress at the inspected zone.…”
Section: Methodsmentioning
confidence: 99%
“…These difficulties have created the need to assess phenomenological methods [1] such as acoustic emissions [8], digital image correlation [9,10], thermography [10,11], X ray tomography [12], electrical resistance [13], and analysis of the surface [14,15,16], among others.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations